University Education Students’ Self-Perceptions of Writing - Gambell, Trevor (Canadian Journal of Education/Revue canadienne de l’éducation, 1991)
University students in preservice education programs write primarily for their professors, whom they see as content experts and evaluators. Consequently, they find writing a difficult and often unrewarding task. This study examines the perceptions of 48 elementary education preservice teachers of their own writing vis-à-vis the written demands of their courses. Students admitted, often tacitly, that their writing difficulties resulted from reliance on the ideas and language of others, an inability or unwillingness to conceptualize an audience, uncertainty about the rhetorical features of expository and argumentative modes, and lack of understanding of a process approach to writing. The study has implications as much for teacher educators as for students in preservice education programs. Les étudiants inscrits dans les programmes de formation des maîtres écrivent essentiellement pour leurs professeurs qu’ils voient comme des experts et des évaluateurs de contenu. Ils considèrent donc la rédaction comme une tâche diffi- cile et peu gratifiante. L’étude dont il est fait état dans cet article analyse les perceptions qu’ont 49 stagiaires au primaire de leur écriture par rapport aux exigences de leurs cours. Les étudiants admettent, souvent tacitement, que leurs difficultés en composition sont causés par divers facteurs : ils se fient sur les idées et le langage des autres, ils sont incapables ou ne veulent pas imaginer leur auditoire, ils connaissent mal les caractéristiques rhétoriques des modes d’expo- sition et d’argumentation et ils ne comprennent les méthodes de rédaction. L’étude peut servir autant aux formateurs qu’aux stagiaires.